(untitled) (Czech Journal of International Relations, 2023)
The Sahel region currently faces various social, political, security, and environmental issues. However, the scientific and media discourse tends to oversimplify the underlying causes of these issues. While some authors attribute them to the heavy impact of climate change-induced scarcity, others focus on political factors such as bad governance. This article aims to merge the perspectives of Environmental Security and Political Ecology into one framework to provide a more holistic explanation of the problems in the Sahel. It shows how local political inequalities, marginalization, economic problems, military coups, corruption, and climate change mutually intersect in a mechanism that creates conflicts and insecurity. This is exacerbated by the geographical character of the Sahel states and their type of governance, which provides an operational space for many armed groups. By understanding the intersection of these conditions, the article contributes to the empirical understanding of the mechanism of conflicts in the Sahel and better conceptualizes the relationship between scarcity, climate change, and conflict.